Probability Distributions Describing Qubit-State Superpositions - Margarita A. Man’ko; Vladimir I. Man’ko (Entropy, 2023)
We discuss qubit-state superpositions in the probability representation of quantum mechanics. We study probability distributions describing separable qubit states. We consider entangled states on the example of a system of two qubits (Bell states) using the corresponding superpositions of the wave functions associated with these states. We establish the connection with the properties and structure of entangled probability distributions.